Barriers and facilitating factors to healthcare accessibility among Nepalese migrants during COVID-19 crisis in Japan: an exploratory sequential mixed methods study - Sushila Paudel; Aliza K C Bhandari; Stuart Gilmour; Hyeon Ju Lee; Sakiko Kanbara (BMC, 2023)
Abstract Background The COVID-19 pandemic has highlighted the need for global unity and timely access to healthcare for all including multilingual and intercultural societies. This study aimed to identify barriers to healthcare access due to the COVID-19 crisis among Nepalese migrants in Japan and explore ways to counter these barriers, both in routine and crisis situations. Methods This study used an exploratory sequential mixed-methods study design. The researchers conducted 11 focus group discussions including 89 participants and an online survey involving 937 respondents. The integration of focus group discussions and logistic regression analysis from the survey was reported via a 'joint display'. Results Twenty-six themes on barriers to and six on facilitators of healthcare accessibility were identified by the focus group discussions among which 17 barriers like lack of knowledge of health insurance, language barriers, lack of hotline services, unawareness of available services, fear of discrimination etc. had significant association in our logistic regression analysis after adjusting for all confounders. Similarly, the only facilitator that had a significant impact, according to the multivariable logistic regression analysis, was receiving health information from Nepali healthcare professionals (OR = 1.36, 95% CI = (1.01 - 1.82), p-value < 0.05). Conclusion The study suggests the need for a crisis information hub which could be coordinated by the Nepal embassy or concerned authorities, flexible policies for active deployment of Nepalese health workers and volunteers, accessible hotlines in the Nepali language, and incorporation of Nepali telehealth services in Japan.